Effect of vehicles on the pH of nanoparticle calcium hydroxide from Indonesian limestone paste: Pengaruh pelarut terhadap pH nanopartikel kalsium hidroksida dari pasta kapur Indonesia - Atia Nurul Sidiqa; Ryan Wibie Fitriantama; Ira Artilia; Myrna Nurlatifah Zakaria; Arief Cahyanto; I Made Joni; Ani Melani Maskoen (Makassar Dental Journal PDGI Makassar, 2023)
Endodontic treatment can be used to treat root canal infections.In endodontic treatment, calcium hydroxide Ca(OH)2 is commonly used as an intracanal medicament, because of its high alkaline pH, which results in antimicrobial properties. Nanoparticles are technological advancements used to improve the antimicrobial properties of Ca(OH)2.The purpose of this study is to determine the effect of particle size on the pH of Ca(OH)2 paste dissolved in various solvents,including distilled water,propylene glycol,and polyethylene glycol with anL/Pratio of 0.8.Atotalof24samplesofCa(OH)2 pastewereplacedinaplastic tube with a height of 10 mm and a diameter of 2 mm and immersed in 10 mL distilled water in an incubator at 37oC.The pH was measured on day1,day7,andday14.One-way Anova (p<0.05) was used to analyze the collected data revealed that conventional Ca(OH)2 and nanoparticles Ca(OH)2 (NCa) had nearly the same pH on day 1,day 7,and day14inallsolvents. NCa had a lower pH than conventional Ca(OH)2 in all samples.It is concluded that Ca(OH)2 particle size did not affect the pH of the Ca(OH)2 paste.